Analysis of the role of PrrA, PpsR, and FnrL in intracytoplasmic membrane differentiation of Rhodobacter sphaeroides 2.4.1 using transmission electron microscopy - Fedotova, Yana (Springer Netherlands, 2013)
Oxygen dictates the catabolic “lifestyle” of Rhodobacter sphaeroides. When it is present, the bacteria are fully equipped for aerobic respiration. When it is absent, the cells outfit themselves to make use of energy-gathering options that do not require oxygen. Thus, while respiring on alternate electron acceptors in the absence of oxygen even in the dark, the cells are fully enabled for phototrophy. PrrA, PpsR, and FnrL are global regulatory proteins mediating oxygen control of gene expression in this organism. For each of these, regulon members include a subset of a cluster of genes known as the photosynthesis genes, which encode the structural proteins and enzymes catalyzing biosynthesis of the pigments of the light-harvesting and reaction center complexes. The complexes are housed in a specialized structure called the intracytoplasmic membrane (ICM). Although details are emerging as to the differentiation process leading to fully formed ICM, little is known of necessary regulatory events beyond changes in photosynthesis gene transcription. This study used transmission electron microscopy toward gaining additional insights into potential roles of PrrA, PpsR, and FnrL in the formation of ICM. The major findings were (1) the absence of either PrrA or FnrL negatively affects ICM formation, (2) the lack of ICM in the absence of PrrA is partially, but not fully reversed by removing PpsR from the cell, (3) unlike R. sphaeroides, ICM formation in Rhodobacter capsulatus does not require FnrL. New avenues these findings provide toward identifying additional genes involved in ICM formation are discussed.